Tourism English Training to Improve Basic Communication Skills of the Tenjolaya Village Community, Ciwidey, Rancabali - Zia Kemala; Aa Permana (Universitas Ibn Khaldun, 2026)
This community service activity aims to improve the basic English communication skills of the community in Tenjolaya Village, Rancabali District, Bandung Regency, in supporting the development of a nature- and culture-based tourism village. The method used is an interactive, practice-based training with a participatory approach, which includes material delivery, conversation simulations (role-play), and evaluation through pre-test and post-test. The main material focuses on basic skills in greeting and welcoming tourists, self-introduction, and providing simple information related to tourism services. The results show an improvement in participants’ understanding and communication skills, as indicated by higher post-test scores compared to pre-test results, as well as increased confidence in conversational practice. The implementation of the activity ran well and smoothly without significant obstacles, with a high level of participant engagement. However, the limited duration of the training, which was conducted in only one day, became a constraint in deepening the material. Therefore, a continuous follow-up training program is needed to strengthen participants’ competencies. Overall, this activity makes a positive contribution to enhancing human resource capacity and supports the development of Tenjolaya Village as a competitive and sustainable tourism village.